Utmost gallantry : the U.S. and Royal Navies at sea in the War of 1812 - McCranie, Kevin D. (Naval Institute Press, 2011)
Focusing on the oceanic war rather than the war in the Great Lakes, this study charts the War of 1812 from the perspectives of the two opposing navies at sea--one of the largest fleets in the world and a small, upstart navy just three decades old. While American naval leadership searched for a means of contesting Britain's naval dominance, the English sought to destroy the U.S. Navy and protect its oceanic highways. Instead of describing battles between opposing warships, McCranie evaluates entire cruises by American and British men-of-war, noting both successes and failures and how they transl.